Khadijah’s Image in 19th Century Orientalism - Ahlam Sbaihat (Al-Jami'ah Research Centre, 2022)
Khadijah, Prophet Muhammad’s first wife, has remained a victim in Latin and vernacular literature in the West until the 18th century. According to texts in Latin and some vernacular languages written and impacted more by the Church mindset, Muhammad is a manipulator man who used Khadijah to gain wealth and power through marriage. However, this image has changed decisively as a result to the new historical approach of the French Historical Scholar School followed at the beginning of the 19th century. The present study investigates the image of Khadijah in French texts based on the image studies analysis. Particularly, forty-nine French texts published in the 19th century were studied and analyzed. The texts include books, dictionaries, encyclopedias, journals of literature and science. The results show that the image of Khadijah has changed drastically. Khadijah, the rich widow made a major contribution to the founding of the new creed mentality of Islam. Khadijah is no longer the persecuted victim of Muhammad; but an intelligent, wise, supporter and loving wife. Moreover, another analysis of these texts shows that since the 18th century, the characters of Muhammad and Khadijah were used in French fantasia that imitates the Arabian Nights.[Istri pertama Nabi Muhammad, Khadijah, masih diceritakan sebagai obyek penderita dalam literatur bahasa Latin dan Eropa hingga abad 18. Berdasarkan teks-teks latin dan yang dipengaruhi oleh mindset gereja, Muhammad merupakan orang yang memanfaatkan perkawinannya dengan Khadijah untuk meraih kemakmuran dan pengaruh politik. Namun gambaran itu perlahan memudar seiring dengan berkembangnya pendekatan sejarah baru para sejarahwan Prancis dan diikuti oleh sarjana lainnya hingga awal abad 19. Pada tulisan ini akan mengkaji gambaran Khadijah dalam teks-teks berbahasa Prancis. Setidaknya ada 49 tulisan yang akan dibahas dan dianalisis termasuk diantaranya, buku, kamus, ensiklopedia, artikel jurnal sastra dan sains. Kesimpulannya menunjukkan bahwa gambaran tentang Khadijah berubah drastis, dia sebagai janda kaya telah memberikan kontribusi besar dalam meletakkan mentalitas baru umat Islam. Khadijah bukanlah obyek penderita, tapi seorang yang pandai, bijak, pendukung utama dan istri yang mencintai suaminya, Muhammad. Selain itu, karakter Muhammad dan Khadijah hingga abad 18 digunakan sebagai fantasi yang disejajarkan dengan kisah Seribu Satu Malam.]